The Effect of the Construction Contract System on the Quality of Contractors' Work in Road and Bridge Construction Projects in Mountainous Papua Province - Yompi Lani; Bernathius Julison; Dewi Ana Rusim; Mujiati Mujiati; Bahtiar Bahtiar (International Journal Labs, 2025)
The Lumpsum contract system with a Fix Price value with the financing system is Contractor's Full Prefinanced (CPF). This system will be implemented for owners to ease costs, considering that financing is charged to contractors 100%. and paid 30 days after the minutes of the PHO were signed by both parties, Rato (20018). One of the contract systems used in the contract for the purchase of a construction project is the Remeasure Contract (Unit Price). Bridge construction infrastructure is one of the land transportation infrastructure that has an important role in the distribution of goods and services as well as mobility for the community and other economic sectors. Therefore, bridge construction plays a very important role in economic growth in a region. From the above background, the author needs to re-analyze a construction project in the Mountainous Papua Province in terms of the quality of work of the contractor, the lumpsum contract system, and the unit price contract system in the bridge construction project. The results of this study are as follows: the effect of the Lumpsum contract system on the quality of contractors' work in road and bridge construction projects is GOOD. The effect of the Unit Price contract system on the quality of contractors' work in road and bridge construction projects is GOOD. There is no effect of the contract system on the quality of contractors' work on road and bridge construction projects in Papua Mountainous Province.